2016
DOI: 10.4236/ce.2016.79139
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Flipped Classroom Mode on the English Pronunciation Course

Abstract: A lot of problems in pronunciation teaching remain unsolved after many years of efforts made by both teachers and researchers. This study is to research into the effectiveness of a comparatively new teaching mode-the flipped classroom-in the English pronunciation course. Mixed methods are adopted in this study in order to seek sufficient evidences for the effectiveness of the flipped classroom teaching mode. The students' final exam scores are compared with those of the students taught with the traditional tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 3 publications
3
14
0
1
Order By: Relevance
“…This finding partially challenges previous studies that found mostly positive results with implementations of the FC (Baepler et al 2014;Zhang et al 2016;Santikarn and Wichadee 2018).It is more consistent with studies that express more caution (Yen et al 2018). Far from arguing that students did not appreciate active learning techniques, such as the FC, our data show students prefer "having mixed class sessions" over "having all flipped-class sessions" (Jenkins 2015: 610).…”
Section: Discussionsupporting
confidence: 84%
“…This finding partially challenges previous studies that found mostly positive results with implementations of the FC (Baepler et al 2014;Zhang et al 2016;Santikarn and Wichadee 2018).It is more consistent with studies that express more caution (Yen et al 2018). Far from arguing that students did not appreciate active learning techniques, such as the FC, our data show students prefer "having mixed class sessions" over "having all flipped-class sessions" (Jenkins 2015: 610).…”
Section: Discussionsupporting
confidence: 84%
“…That was not surprising as most students by the end of the year were given many opportunities to practice speaking the language, recording it and getting feedback from peers and the teacher on how to better improve their vocabulary use and speaking skills in general. Students use of more accurate structures coincided with the findings of Al-Harbi & Alshumaimeri (2016), their English pronunciation (Zhang et al, 2016) and their overall English proficiency have improved as the results of Wu & Yang (2017) pointed out.…”
Section: Interpretationssupporting
confidence: 66%
“…Implementing the flipped classroom in English language teaching enables teachers to reach students with different learning abilities, enhances classroom management and reduces negative behavior tremendously (Cockrum, 2013) , as it allows teachers to have more interaction time to spend with each student, which improves teacher-students relationships (Basal, 2015;Bergmann & Sams, 2015;Sung, 2015;Zhang & Wu, 2016)), In addition, the flipped classroom is proved to increase students' creative thinking (Al-Zahrani, 2015), listening and writing skills (Ahmad, 2016), reading comprehension (Huang & Hong, 2016), grammar (Al-Harbi & Alshumaimeri, 2016), English proficiency (Wu, Hsieh, & Yang, 2017), and English pronunciation (Zhang et al, 2016).…”
mentioning
confidence: 99%
“…As such, different strategies were developed and used to improve not native-like pronunciation of the target language by the SL learners but rather instead to enable the learners to perform well in spontaneous speech (Brown, 1992 andPawlak, 2010). However, these strategies according to Zhang et al (2016) have not always proved to be successful in the history of teaching, especially in the methods of teaching pronunciation. Students usually taught to learn pronunciation through audio recordings of the materials pronounced by native speakers and the students have to imitate what they hear of the learned language.…”
Section: Introduction 11background Of the Studymentioning
confidence: 99%
“…Therefore, the current study emerges as a one to fill the gap of the effect using a form of new technologythe flipped classroom. Especially and more importantly, when using such techniques in teaching pronunciation materials are seldom or rare (Zhang et al: 2016). It is with an interest to apply this kind of study-using the flipped classroom to see the level of effectiveness on Iraqi EFL learners by which no previous studies have been conducted to meet this gap knowledge.…”
Section: Introduction 11background Of the Studymentioning
confidence: 99%